Impact of job design and motivation on employee’s in public sector,Putrajaya / Zarina Begum Ebrahim and Khairul Nizam Zakaria - Ebrahim, Zarina Begum; Zakaria, Khairul Nizam; Sauid, Muna Kameelah; Mustakim, Nurul Ain; Mokhtar, Noorzalyla (Universiti Teknologi MARA Cawangan Pahang, 2019)
Designing interesting jobs are becoming a major concern among employers as one way of enhancing the employee’s motivation. This study seeks to find the Impact of Job Design on Employee’s Motivation amongst employee’s in public sector at Putrajaya. The sample sizes of 350 respondents were randomly selected to participate in this study. The results of the study revealed that, elements of Job Design which is Skill Variety, Task Identity, Task Significance, Autonomy, and Feedback is significantly correlates with employee’s motivation. However, among the five elements, only Skill Variety, Task Identity, Autonomy, and Feedback have most impact on employee’s motivation. Based on the yielded results, several recommendations were pointed out which is, employers need to focus on the areas in which affects the employee’s motivation most and improve the areas which are not. Future study should also be conducted in the private sector on the similar area of study or different sector.